Regional foot pressure during running, cutting, jumping and landing - Orendurff, M. S.; Rohr, E. S.; Segal, A. D. M; Medley, J. W.; Green, J. R.; Kadel, N. J. (The American Journal of Sports Medicine, 2008)
Evaluating shoes during sport-related movements may provide a better assessment of plantar loads associated with repetitive injury and provide more specific data for comparing shoe cushioning characteristics.